The Potential of Beets Ice Cream on Increasing the Number of Erythrocytes for Postpartum Women With Anemia - Rahmi, Sania Lailatu; Rifni, Indrie Aulia; Rahmiati, Eka (LPPM Universitas Prima Nusantara Bukittinggi, 2023)
Background : Anemia during the postpartum period is one of the causes of maternal death in Indonesia with an incidence rate of up to 30% cases. Most of them are caused by iron deficiency. It can disrupt oxygen transport due to the function of iron as a form of hemoglobin and erythrocyte.Goals: To explain the effect of beets ice cream on the increasing of erythrocyte levels in postpartum mothers with anemiaMethod: This research is a Quasi experiment type by using a pretest-posttest with a controlled group. The sample of this study was 30 respondents of postpartum mothers with anemia and then divided into 2 groups, they are 15 respondents for treatment groups and 15 respondents for controlled groups. The sampling technique used in this study was accidental sampling and the variables in this study were giving beets ice cream for 7 days as the independent variable and the level of erythrocytes as the dependent variable. The measurement tools for this study included observation sheets, blood sampling tools, and hematology analyzers. The data in this study were analyzed with paired t-tests, independent t-tests, and one-way ANOVA to determine the effect of therapy on the increase in erythrocytes.Result: 11 grams of beets ice cream treatment for 7 days toward postpartum mother can increase the level of erythrocytes up to 1,2907 with a p-value of 0,000 (p< 0,05). One-way ANOVA test shows a significant result of erythrocytes levels for a group of sampling with (p=0,004).Conclusion:11 beets ice cream given to postpartum mothers with anemia